The Altar Steps - MacKenzie, Compton, 1883-1972 (Salt Lake City, UT : Project Gutenberg, 2005)
"The Altar Steps" by Compton MacKenzie is a novel written during the early 20th century. The story begins in a London mission setting, focusing on the character of a little boy named Mark Lidderdale, whose life is intertwined with the church and the complexities of his family's dynamics, including his father, a missioner, and mother, as they navigate their roles in the ecclesiastical setting of that era. The opening of the book portrays a vivid glimpse into Mark's childhood filled with a blend of innocence and fear, encapsulated in his night-time worries and whimsical thoughts surrounding his experiences with the Bishop's impending visit. As he wrestles with ideas of disaster and divine protection, readers are introduced to his loving, yet perhaps overly cautious mother, alongside a father who is deeply invested in his ecclesiastical duties. The transition into the life of the Lidderdale family hints at deeper themes of parental expectations and the challenges of faith and duty, setting the stage for Mark's growth in a world deeply influenced by religious convictions and personal aspirations. (This is an automatically generated summary.)
Release date is 2005-01-20
Produced by Steven desJardins and Distributed Proofreaders
Keywords: Clergy -- England -- Fiction; Children of clergy -- Fiction